Comparison of Analytic Indices of In-person vs. Online Exams in an Iranian Medical University in the Academic Year 2020 - Reza Malek Pourafshar; Reza Shojaeipour; Payam Khazaeli; Azam Bazrafshan; Amin Beigzadeh; Mahmoud Reza Dehghani (Kerman University of Medical Sciences, 2020)
Background: Currently, many medical universities in Iran use e-learning programs to educate and evaluate students. This teaching and assessment method is highly significant during the coronavirus epidemic. Objectives: The present study was conducted to compare the analytic indices of in-person vs. online exams at the Kerman University of Medical Sciences, (KUMS), Iran. Method: This descriptive-analytical cross-sectional study was conducted in 2020. The study samples included all exams given at the KMUS and midterm exam scores obtained from in-person and online courses in the first and second semesters in the academic year 2019-2020. The exams were selected based on courses, and the same courses were offered both in-person and online; thus, only one group was studied. Course exam indicators, including difficulty and discriminative index, were examined. Data analyzed using SPSS software version 22. Results:  The mean of the difficulty index related to in-person and online exams were (0.62 ± 0.1) and (0.68 ± 0.1), respectively. (P=0.01). The mean of the discriminative index related to in-person (0.30± 0.07) and online (0.33± 0.08) exams had no statistically significant difference (P˃0.05). The frequency of easy questions in online exams was significantly higher, (55% vs. 43%) (p = 0.008). The frequency of questions with an appropriate discriminative index was significantly higher for in-person exams compared to online exams (58% vs. 54%) (p = 0.01). Conclusion: The difficulty index was acceptable and appropriate for both in-person and online exams. Both exams had appropriate quality according to the discriminative index .Therefore, it seems that e-learning programs and assessments can be a good alternative to in-person teaching in emergencies.